Network Structural CNTs Penetrate Porous Carbon Support for Phase‐Change Materials with Enhanced Electro‐Thermal Performance. (14th April 2020) - Li, Ang; Dong, Cheng; Dong, Wenjun; Yuan, Fugen; Gao, Hongyi; Chen, Xiao; Chen, Xiao‐Bo; Wang, Ge
Abstract: Electro‐thermal phase‐change materials (PCMs) enable continuous operation of heating‐related processes, which is urgently required for modern thermal‐management devices. Driven by the unmet needs to develop promising electro‐thermal PCMs with low operation voltage and high electro‐thermal storage efficiency simultaneously, unique ZIF@MOF‐derived carbon‐nanotube (CNT)‐penetrated porous carbon supports for electro‐thermal PCMs are introduced. The network structure of the support decreases the resistivity of the composite and ensures a low operation voltage. Furthermore, abundant CNT cores in porous carbon shells facilitate interfacial interaction between the PCMs and the support and realize a rapid heat transformation. It is noted that low thermal conductive porous carbon shells prevent convective heat dissipation at the CNT‐air interface to a great degree which leads to enhanced electro‐thermal storage efficiency. Consequently, the obtained electro‐thermal PCMs exhibit a low operation voltage of 1.1 V and a record‐high electro‐thermal storage efficiency of 94.5%, which shows great potential in thermal management of electronic devices. Abstract : Unique ZIF@MOF‐derived carbon‐nanotube‐penetrated porous carbon supports are synthesized for electro‐thermal PCMs, which show an ultralow operation voltage of 1.1 V and a record‐high electro‐thermal storage efficiency of 94.5%. This study provides great insights into the thermal management of electronic devices.